Políticas de Ampliação da Jornada Escolar (PAJEs) no Brasil: metapesquisa de Teses e Dissertações - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This study aimed to analyze conceptual and terminological aspects of the knowledge production on Policies Extending School Time (PAJEs, Brazilian acronym for Políticas de Ampliação da Jornada Escolar) in Brazil based on meta-research of Theses and Dissertations. The epistemic and methodological framework included contributions by Pierre Bourdieu (epistemological surveillance and reflexivity) and Basil Bernstein (recontextualization of the pedagogic discourse). The meta-research developed enabled the exploration of the main trends, theoretical-epistemological perspectives, and conceptual and terminological aspects of Theses and Dissertations on the issue (1992-2019). The first stage of the investigation involved the search for Theses and Dissertations originated in Brazilian Postgraduate Programs carried out in the Coordination for the Improvement Higher Education Personnel (CAPES, Brazilian acronym for Coordenação de Aperfeiçoamento de Pessoal de Nível Superior) repository. This search resulted in the listing and characterization of 704 Theses and Dissertations. The second phase involved the analysis of 38 Theses selected for the meta-research. This study found out that there are five different concepts of PAJEs used in Theses and Dissertations, namely, a) Full Time School; b) Extended Time; c) Full Education; d) Full Time Education; and e) Full Time Full Education. In addition, we understand that the clarification of the PAJE concept under investigation by the researcher contributes to a better understanding of the object of study. Most productions addressing PAJEs are empirical, based on qualitative approach and local coverage, and are founded on a plural epistemological perspective (combined theorization) showing surface epistemological density and analytical descriptive level. Regarding the conceptual/terminological aspect, most Theses do not present a concept of Education Policy and a significant number does not show coherence in the use of terms related to studies on PAJEs. For being a sub-field of the Education Policy, which is still being built up, incompleteness and uncertainty are observed regarding the terminology and the concepts employed in the analysis of Policies Extending School Time. The research results revealed some of the needs to be considered in this area, which include: a) a permanent dialogue between agents and researchers who take part in the official recontextualizing field (ORF) and the pedagogic recontextualizing field) ; b) definition of guidelines for the implementation of PAJEs by means of education laws at the national level, so that they are structured as State policies; and c) reflection upon the concept of Full Education and its contemporary practice. Other findings refer to the importance of research on PAJEs and the need for continuous improvement of the studies on this theme. This is a set of education policies, which are vital to make the schooling process more satisfactory and which demand a review of all curriculum conception, time distribution, methodologies, and evaluations.
Keywords: Ampliação do tempo escolar; Educação em tempo integral; Política Educacional; Extending School Time; Full Time Education; Education Policy; CNPQ::CIENCIAS HUMANAS::EDUCACAO